Diversity of the VIR basil (Ocimum basilicum L.) collection by morphological and phenological features - A. B. Kurina (Овощи России, 2022)
Relevance. Basil is one of the most popular aromatic plants grown in the world. Various species and forms of Ocimum spp. differ in the nature of growth, color and aromatic composition. The VIR basil collection is represented by 452 accessions of six species from 55 countries. The expansion of the assortment of basil, as well as the identification of competitive adaptive cultivars with high economically valuable traits, determines the need to study and identify promising species and forms of Ocimum spp. The purpose of our work was to study accessions of basil (Ocimum basilicum) from the VIR collection by morphological and phenological traits and to identify accessions that have a complex of economically valuable traits for further use in the breeding.Materials and methods. The studies were carried out at the Federal Research Center N. I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR) at the VIR Pushkin and Pavlovsk Laboratories in 2019-2021 in open ground conditions. The material of the study was 66 accessions of the VIR basil collection of various agrobiological status and ecological and geographical origin. When analyzing the material, phenological observations, biometric measurements and morphological description of plants were carried out. These measurements were carried out in the phase of mass flowering.Results. As a result of the study, the degree of variability of the main phenological and morphological features was revealed. Accessions of basil were selected according to such traits as early maturity, plant height, weight of one plant and cold resistance, which can be used as starting material for breeding. The studied accessions are grouped into 7 varieties of two subspecies (subsp. basilicum and subsp. minimum): var. basilicum, var. glabratum, var. purpurescens, var. majus, var. diforme, var. minimum and var. chamaeleonicum, and their characteristics are given.